Enhancing primary school students' competencies in step by step controllable argumentation using a new learning environment - Dekriati Ate (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2021)
For the goal of raising the mathematical performance of students, the quality of teaching has to be improved in the direction that critical thinking and a step-by-step controllable argumentation have to be established. Metacognitive activities of teachers and students can support this. The goal of the design research presented in this paper is to show how metacognitive activities in classroom discussions can be fostered and the mechanisms can be uncovered. For this purpose, on the one hand, a new learning environment - designed for learning addition and subtraction of integers in grade four – has been created. On the other hand, the teacher and the students have been consequently educated to practice new behavior during the lessons. This pilot study is carried out in Sumba, in a regular class, grade four, consisting of 28 students. The lessons had been video graphed; selected pieces of the public discussions have been transcribed. Teacher’s and learners’ utterances and their interplay have been classified using a particular coding system developed for those purposes. The pattern of classifications has been the basis for interpreting the metacognitive-discursive learning culture. One result of the study is that students even in grade four accept such a learning environment; they practice inventing and analyzing strategies in this field of algebra as it would be a game with step-by-step controllable argumentations. After that, an astonishingly short time of educating students to practice metacognitive activities, both in oral discussions as well as in written answers to relevant formulated questions.